Development of an Agriculture Mobile Learning System using the Peer-To-Peer (P2P) Model - Delima, Rosa; Wibowo, Argo (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
E-learning is a learning process that utilizes an internet medium that connects teachers and students using multimedia-based teaching materials. M-learning is a learning model that has many similarities with e-learning; only the M-learning interaction model between teachers, students, and teaching materials is facilitated by mobile devices. Currently, quite a lot of mobile learning is being developed in Indonesia, but most of the research focuses on students. Not many have developed M-learning for the general people with the specific content or teaching materials in agriculture. An agriculture learning system is developed by applying the pear-to-pear (P2P) model between teachers and participants. The system applies two platforms, namely web and mobile. Admins and teachers use the web application, while the mobile application is used by the participants. Based on the system testing results, it is known that all functions in the system have been running well. Evaluation of the system's suitability with user requirements also shows that the system has accommodated all requirements.